Adipose tissue macrophages in insulin-resistant subjects are associated with collagen VI and fibrosis and demonstrate alternative activation - Spencer, Michael; Yao-Borengasser, Aiwei; Unal, Resat; Rasouli, Neda; Gurley, Catherine M; Zhu, Beibei; Peterson, Charlotte A; Kern, Philip A (American journal of physiology: endocrinology and metabolism, 2010)
Adipose tissue macrophages are associated with insulin resistance and are linked to changes in the extracellular matrix. To better characterize adipose macrophages, the extracellular matrix, and adipocyte-macrophage interactions, gene expression from adipose tissue and the stromal vascular fraction was assessed for markers of inflammation and fibrosis, and macrophages from obese and lean subjects were counted and characterized immunohistochemically. Coculture experiments examined the effects of adipocyte-macrophage interaction. Collagen VI gene expression was associated with insulin sensitivity and CD68 (r = -0.56 and 0.60, P < 0.0001) and with other markers of inflammation and fibrosis. Compared with adipose tissue from lean subjects, adipose tissue from obese subjects contained increased areas of fibrosis, which correlated inversely with insulin sensitivity (r = -0.58, P < 0.02) and positively with macrophage number (r = 0.70, P < 0.01). Although macrophages in crownlike structures (CLS) were more abundant in obese adipose tissue, the majority of macrophages were associated with fibrosis and were not organized in CLS. Macrophages in CLS were predominantly M1, but most other macrophages, particularly those in fibrotic areas, were M2 and also expressed CD150, a marker of M2c macrophages. Coculture of THP-1 macrophages with adipocytes promoted the M2 phenotype, with a lower level of IL-1 expression and a higher ratio of IL-10 to IL-12. Transforming growth factor-β (TGF-β) was more abundant in M2 macrophages and was further increased by coculture with adipocytes. Downstream effectors of TGF-β, such as plasminogen activator inhibitor-1, collagen VI, and phosphorylated Smad, were increased in macrophages and adipocytes. Thus adipose tissue of insulin-resistant humans demonstrated increased fibrosis, M2 macrophage abundance, and TGF-β activity.